Pengaruh Lingkungan Kerja, Motivasi Kerja dan Stress Kerja terhadap Kinerja Karyawan pada CV Swet Seventeen Sidoarjo - Siti Nur Hasanah; Budi Prabowo (LPPM Institut Nasional Laa Roiba Bogor, 2023)
This study aims to determine: (1) To determine and analyze the effect of work environment, work motivation and work stress simultaneously on employee performance at CV Sweet Seventeen employees. (2) To find out and partially analyze the effect of the work environment on employee performance at CV Sweet Seventeen. (3) To find out and analyze the effect of work motivation partially on employee performance at CV Sweet Seventeen employees. (4) To find out and partially analyze the effect of work stress on employee performance at CV Sweet Seventeen employees This research method uses quantitative methods. The research sample was drawn using the saturated sampling method totaling 35 people taken from the entire population of employees of CV Sweet Seventeen, Sidoarjo. The data analysis technique used is multiple linear regression. Based on this research, Fcount, namely H0 is rejected and H1 is accepted, so it can be concluded that the variables of work environment, work motivation and work stress have a significant influence on the performance of CV Sweet Seventeen employees. The results of Tcount for the work environment variable H0 are accepted and H1 are rejected, so it can be concluded that partially there is an insignificant positive effect on employee performance. The results of Tcount work motivation variable H0 are rejected and H1 are accepted, so it can be concluded that partially has a significant positive effect on employee performance. Tcount work stress variable H0 is rejected, so it can be concluded that partially there is a significant effect on employee performance at CV Sweet Seventeen, Sidoarjo. Keywords: Work Environment; Work Motivation; Work Stress; Employee Performance